Summary of instrumentation installed in boreholes drilled into Khumbu Glacier, Nepal, in 2017 and 2018 as part of EverDrill research project - Hubbard, Bryn; Miles, Katie; Quincey, Duncan; Miles, Evan (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
The dataset lists information about the instrumentation of boreholes drilled into Khumbu Glacier, Nepal. Boreholes were drilled in May 2017 and May 2018 to investigate the internal properties of Khumbu Glacier, specifically ice thickness, temperature, deformation and structure, as part of the NERC-funded 'EverDrill' research project. The information provided includes each borehole's ID, length, location, elevation and instrumentation, including the type and depth of each sensor. Funding was provided by the NERC grant NE/P00265X/1 and NE/P002021/1. : Borehole information was collected while boreholes were drilled using a hot-water drill in 2017 and 2018 on Khumbu Glacier, Nepal. Location and elevation were measured with a handheld GPS unit. Borehole depth was measured from the length of drilling hose in the borehole at the time when drilling progress ceased, and confirmed from the length of sensor cable lowered into the borehole. The type, and depth at which each sensor was installed is detailed, as well as each sensor ID.